Nutrition and Avoidance Diets in Children With Food Allergy - Corica, Domenico; Aversa, Tommaso; Caminiti, Lucia; Lombardo, Fortunato; Wasniewska, Malgorzata; Pajno, Giovanni Battista (Frontiers in Pediatrics, 2020)
Food allergy (FA) is a significant health issue which considerably influence quality of life of both children and their family. The increasing prevalence of FA, documented in the last three decades, has led to reassess FA prevention strategy and particularly to give up the approach based on delaying the introduction of potential food allergens. Several observational and interventional studies demonstrated a potential effectiveness of early food introduction strategy in FA prevention, although strong evidence from randomized controlled trials are lacking and, sometimes, contrasting. Current approach to FA is mainly based on avoidance diet and use of rescue medications in case of allergic reaction, although active allergen immunotherapy has recently become an increasingly important therapeutic strategy to approach IgE-mediated FA, potentially able to induce improvement trough desensitization to a specific food. This review provides an overview on historical evolution of recommendations about FA and on evidence published in the last 15 years on nutritional intervention strategy, i.e. early introduction of allergen or avoidance diet, in prevention and management of IgE-mediated and non-IgE-mediated FA in children.